2020
DOI: 10.47895/amp.v54i0.1558
|View full text |Cite
|
Sign up to set email alerts
|

Should IgM/IgG rapid test kit be used in the diagnosis of COVID-19?

Abstract: KEY FINDINGS Current evidence does NOT support use of IgM/IgG rapid test kits for the definitive diagnosis of COVID-19 in currently symptomatic patients. • The present standard for diagnosis of COVID-19 is through qualitative detection of COVID-19 virus nucleic acid via reverse transcription polymerase chain reaction (RT-PCR). • Due to long turnaround times and complicated logistical operations, a rapid and simple field test alternative is needed to diagnose and screen patients. • An al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…RAT testing is based on IgM/IgG antibodies. Low specificity (77.8%) and sensitivity (18.8%) have been the main drawbacks of this method [4]. Therefore, emphasis is being given to other methods of testing that might be more accessible and less expensive in the future.…”
Section: Introductionmentioning
confidence: 99%
“…RAT testing is based on IgM/IgG antibodies. Low specificity (77.8%) and sensitivity (18.8%) have been the main drawbacks of this method [4]. Therefore, emphasis is being given to other methods of testing that might be more accessible and less expensive in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a shortage has always been observed of RT-PCR test kits worldwide. Just like RT-PCR, IgM/IgG antibodies tests have their own disadvantages with sensitivity and specificity being as low as 18.8% and 77.8% respectively in initial screening of COVID-19 [4]. Although CT scans and chest X-rays images based on Machine learning [5] have shown positive results, however these tests are not much useful due to high dosage of radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, antibodies are detected in the patient's blood samples, depending on factors such as age, nutrition, disease severity and medications. However, recent studies have shown that the immune response is very weak, late or even absent in many cases of patients confirmed with Covid-19 [12][13][14][15][16][17][18]. This means that this type of detection is often only possible in cases of recovered patients.…”
Section: Introductionmentioning
confidence: 99%